Jak daleko jesteśmy z nauką? Wpływ polityki na wartości poznawcze w wybranych artykułach zamieszczanych w "Magazynie Polskim" w 1988 roku = How far are we with science? The impact of politics on the cognitive values in chosen articles of "Magazyn Polski" in 1988 - Kępa, Łukasz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The subject of the article is the research trying to present the way politics influence cognitive value. Research material is based on articles published in "Magazyn Polski" in 1988. The first part concentrates on the definition of the value, shows chosen typologies of value and brings closer the concept of cognitive value.
Keywords: odkrycia; socjalizm; nauka; polityka; propaganda; PRL; discoveries; politics; pseudo-scientific; socialist system